Energy and Exergy Efficiency of Double Slope Passive Solar Still - Saragi, Jandri Fan HT; Damanik, Wawan Septiawan (Universitas Negeri Malang, 2020)
Solar desalination functions to filter water, both sea water and brackish water, to produce clean water that is fit for consumption with energy from the sun. Solar energy is a renewable energy source that has been widely studied for its use. One of its uses is in a double slope passive solar still where the sun is the main source. Energy and exergy obtained from solar energy are not all used to evaporate water in the desalination system, so it is necessary to calculate efficiency energy and exergy in the system. This study aims to obtain data on the amount of efficiency energy and exergy from the double slope passive solar still as well as the factors that affect efficiency energy and exergy. The results showed that energy efficiency was in the range of 30.20% to 55.15% and exergy efficiency was in the range of 0.93% to 5.36%. The factors that influence the amount of energy efficiency and exergy are solar intensity, basin area, basin cover area, amount of water produced and ambient temperature.